Unexpected two-step response in AlGaAs/GaAs heterostructure-based SBD. Issue 2 (2nd April 2020) - Chatterjee, Soumyadip; Mahata, Mihir Kumar
ABSTRACT: While analyzing current–voltage characteristics in the forward region of the MBE grown Al/Al0.3 Ga0.7 As/GaAs Schottky barrier diode (SBD) at a higher voltage it has been found out that for a range of voltage the current does not change exponentially, rather the current seems to be saturated. In this work, the cause of such a saturation is analyzed with the help of a two-diode model. Here another secondary diode is assumed to be formed due to improper ohmic contact. Possibilities of having this kind of unwanted saturation in devices with proper ohmic contacts have also been analyzed.